EFFICACY AND ADVERSE EFFECTS OF ORAL IRON CHELATOR DEFERIPRONE (L1, 1,2- DIMETHYL-3-HYDROXYPYRID-4-ONE) IN PATIENTS WITH BETA THALASSAEMIA MAJOR IN PAKISTAN - Ayyub, Muhammad; Ali, Waqar; Anwar, Masood; Waqar, Amin; Khan, M. Naeem; Ijaz, Aamir; Hussain, Tassawar; Hussain, Shujaat (Journal of Ayub Medical College Abbottabad, 2005)
Background: Deferiprone (DFP,L1) is a bidentate oral iron chelator which binds to iron in a 3:1 ratio. It has the potential advantage of reduced cost and increased compliance. We conducted a study in order to determine the efficacy and adverse effects of DFP in Pakistani thalassaemic patients. Methods: A group of 26 thalassaemic patients entered the study during the period Jan 1999 to Aug 2002. DFP supplied by Lipomed, Switzerland was given at a daily dose of 75 mg/kg/day (range 50-75 mg/kg/day). After giving informed written consent all the patients were subjected to clinical examination and investigations for monitoring the response. Blood complete picture, liver function tests, blood urea & creatinine, antinuclear factor antibodies (ANF) were tested in all cases before starting DFP treatment. Results: The patients ages ranged from 11 to 27 years, 16 were male and 10 were female. Initial serum ferritin level ranged from 3100-8800 Î¼g/l, mean serum ferritin level was 7129±1467 Î¼g/l (95% CI 6536 - 7721 Î¼g/l). ECG and Echocardiography was performed in all cases and in 11 cases Cardiac Multigated acquisition (MUGA) Scan was also performed and six patients with impaired left ventricular function were identified. Four patients were lost to follow up and one patient died due to cardiomyopathy. Among the remaining 21 patients serum ferritin levels dropped to 1900Î¼g/l to 5600Î¼g/l with mean level of 4288 Î¼g/l (95%CI 3874 - 4702 Î¼g/l), SD 911 Î¼g/l. Significance of difference was (p < 0.001) by Paired samples '˜t' test. Six patients had gastrointestinal symptoms along with two having arthropathy. ANF positivity was not detected in any patient while on DFP treatment. Similarly, agranulocytosis was not detected in any patient. Conclusion. Mean serum ferritin level estimated at the start of trial was 7129 Î¼g/l. This shows that Pakistani thalassaemic patients are quite iron overloaded due to socioeconomic reasons that are peculiar to our setup. In this study DFP was well tolerated and caused fewer side effects. It had much better patient compliance and was effective in lowering serum ferritin level in previously most poorly chelated patients. Keywords: Thalassaemia, Deferiprone, Transfusion iron overload, Cardiomyopathy, Demography